Análise e otimização dos algoritmos para angiografia por tomografia por coerência óptica e desenvolvimento de Phantom por impressão 3D - (:unkn) unknown (Universidade Brasil, 2021)
Skin grafts are surgically applied to repair skin lesions such as burns and extensive necrosis. The success of this surgical procedure is associated with good blood supply in the grafted region. Thus, the assessment of angiogenesis during the tissue repair process is essential for its prognosis. The development of non-invasive evaluation techniques is extremely important for the success of this procedure. One of the promising techniques is Optical Coherence Tomography Angiography (OCT-A), a non invasive technique that can be used to obtain images of the vascularization of biological tissues. The adoption of this technique as a clinical practice in dermatology involves reducing its cost, and the use of equipment with a low acquisition rate (low cost) is a possible path. Thus, this work aimed to implement and optimize algorithms for obtaining angiography images by optical coherence tomography (OCT-A) for applications in images acquired with low acquisition rate and cost equipment. To test those methods, it is requiring the use of phantom that simulate the behavior of the microvascular system. Thus, this work also aimed at the development of a phantom to simulate a microvascular system using 3D printing technology. Phantoms containing microchannels were designed and printed on polylactic acid (PLA) using a 3D printer by fused filament deposition. These PLA phantoms were imaged with the OCT system (OQLabScope - Lumedica, USA). Seven different OCT-A methods were implemented (HFM, STS, CM, SV, OSV, ISC and UHS-OMAG) and compared against their processing time, signal-to-noise ratio, contrast, and contrast-to-noise ratio. The OSV and CM methods showed better overall performance based on these parameters, but CM shown higher processing time. An optimization of the CM method was proposed in this work, reducing the processing time by 99.2%, a significant gain for the algorithm that presented better performances in contrast.
Keywords: Tomografia por coerência óptica (OCT); Angiografia OCT (OCT-A); Phantom de microcanais; Mapa de correlação otimizado; Engenharia Biomédica (Bioengenharia)